Asphaltene detection using surface enhanced Raman scattering (SERS)1. Issue 33 (28th April 2015) - Alabi, O. O.; Edilbi, A. N. F.; Brolly, C.; Muirhead, D.; Parnell, J.; Stacey, R.; Bowden, S. A.
<x xml:space="preserve">Abstract</x> Surface enhanced Raman spectroscopy using a gold substrate and excitation at 514 nm can detect sub parts per million quantities of asphaltene and thereby petroleum.